Dyslipidemia in adults and genetic polymorphism in the mevalonate kinase gene, a systematic review (Research, Society and Development, 2021)
The presence of mutations in dyslipidemia-related genes is of great importance for the outcome of procedures on patients with elevated levels of HDL cholesterol. This systematic review aims to describe the genetic variants in the mevalonate kinase genes in adults with dyslipidemia. A systematic search of the following databases was conducted: Scopus, Web of Science, Google Scholar and Bireme, using the keywords: "Mevalonate Kinase Gene", "Dyslipidemia", "Genetic Polymorphism", linked using the term "AND". The inclusion criteria consisted of articles published between 2008 and 2018, written in Portuguese or English, while the exclusion criteria were the removal of duplicated articles, books, theses and bibliographic reviews, tests not conducted on humans, tests conducted on children and other genes evaluated. The articles listed in this review demonstrate the role of the genetic polymorphism of the mevalonate-kinase gene (MVK) in an adult population. A comparison of results from different studies is often complicated because of the diverse study variables such as: tests used, population studied. The studies described in this review demonstrated that there is an association between genetic profiles and dyslipidemia. Many studies have shown that, besides the external factors and individuals’ behavioral habits, the presence of mutations in the mevalonate kinase gene is associated with dyslipidemia.